Metabolic engineering of Saccharomyces cerevisiae for co-production of ethanol and 3-methyl-1-butanol from sugarcane molasses - Sasha Yogiswara; Jonas Rombout; Giovanni Micharikopoulos; Sam De Craemer; Beatriz Herrera-Malaver; Lotte van Landschoot; Sofie Mannaerts; Marcelo do Amaral; Karin Voordeckers; Stijn Spaepen; Jan Steensels; Quinten Deparis; et al. (Biotechnology for Biofuels and Bioproducts)
Abstract 3-Methyl-1-butanol (3MB) is a promising renewable solvent, drop-in fuel, and precursor for various industrial products, including flavors, fragrances, and surfactants. Due to the myriad of intertwined biosynthetic pathways that share metabolic precursors, conventional metabolic engineering strategies to overproduce 3MB in yeast have typically resulted in yields that are far too low for economic viability. However, because 3MB is naturally produced by yeast, 100 million liter of 3MB are already produced annually as a byproduct of bioethanol fermentations. Despite its significant commercial value, this 3MB fraction is currently discarded due to its low relative concentration within the fusel alcohol mixture. Here, we present a novel strategy to produce 3MB along with the conventional bioethanol fermentation, leveraging the existing bioethanol industry by valorizing the discarded fusel alcohol byproduct stream. We first identified a robust industrially relevant chassis strain and explored different strategies to alleviate the valine and leucine feedback inhibition within the 3MB pathway, showing that mutating the leucine-inhibition site of Leu4p increased 3MB yield by 2.9-fold. Finally, we tested in silico-predicted gene deletion targets to reduce the byproduct acetate. Our final engineered strain achieved a 4.4-fold increase in 3MB yield compared to the wild type (1.5 mg/g sugars), average productivity of 5 mg/Lh, and a 3MB proportion increase from 42 to 71% within the fusel alcohol mix, while ethanol production remained comparable to the Ethanol Red® industrial reference. Our study thus opens a new route for co-producing 3MB and ethanol from sugarcane molasses in Saccharomyces cerevisiae, laying the groundwork toward an economically viable and sustainable approach for 3MB production alongside existing bioethanol production. Graphical Abstract